Antimicrobial Activity of Ethanol Extract of Sea Pandan Leaves (Pandanus odorifer) Against Staphylococcus aureus and Escherichia coli - Rizki, Muhammad Ikhwan; Sari, Anna Khumaira; Rahma, Salsabila Fadiya; Rahmatullah, Satrio Wibowo; Izma, Hayatun (Jurnal FARMASIMED (JFM), 2024)
Sea pandan (Pandanus odorifer) is used in traditional medicine in India. Sea pandan is efficacious in treating pain, parasites, digestive, liver, and cognitive disorders. Sea pandan is found in coastal areas in South Kalimantan. Sea pandan contains flavonoid compounds that have the potential to be antimicrobials. This study aimed to determine the antimicrobial activity of sea pandan leaf extract. The study began with sample preparation, which included washing the leaves, drying them using an oven, refining the particle size, extracting 70% ethanol, and evaporating the solvent until a thick extract was obtained. Total flavonoid levels in sea pandan leaf extract were determined using the colourimetric method using quercetin standards. Antimicrobial testing was conducted using the diffusion method at concentrations of 30%, 40%, and 50% against Staphylococcus aureus and Escherichia coli. The positive control used was chloramphenicol. The determination of the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values ??was carried out using the dilution method. The results showed that sea pandan leaf extract contains phenolics, flavonoids, saponins, steroids, and tannins. The total flavonoid content in sea pandan leaf extract is 10.01% w/w equivalent of quercetin. The antimicrobial activity of sea pandan leaf extract against Staphylococcus aureus bacteria is 10.15 - 25.36 mm, while against Escherichia coli in the range of 8.15 - 23.16 mm. Ethanol extract of sea pandan leaves at a concentration of 50% is included in the very strong category in inhibiting Staphylococcus aureus and Escherichia coli. Ethanol extract of sea pandan leaves has an MIC value of 7.5% on Staphylococcus aureus and 15% on Escherichia coli. MBC of sea pandan extract is 15% on Escherichia coli bacteria. This study concludes that the ethanol extract of sea pandan leaves has antimicrobial activity against Staphylococcus aureus (bacteriostatic) and Escherichia coli (bactericidal).